Pragmatic Realism, Religious Truth, and Antitheodicy : On Viewing the World by Acknowledging the Other - Pihlström, Sami (Helsinki University Press, 2020)
As a traditional theological issue and in its broader secular varieties, theodicy remains a problem in the philosophy of religion. In this remarkable book, Sami Pihlström provides a novel critical reassessment of the theodicy discourse addressing the problem of evil and suffering. He develops and defends an antitheodicist view, arguing that theodicies seeking to render apparently meaningless suffering meaningful or justified from a ‘God’s-Eye-View’ ultimately rely on metaphysical realism failing to recognize the individual perspective of the sufferer. Pihlström thus shows that a pragmatist approach to the realism issue in the philosophy of religion is a vital starting point for a re-evaluation of the problem of theodicy. With its strong positions and precise arguments, the volume provides a new approach which is likely to stimulate discussion in the wider academic world of philosophy of religion. Sami Pihlström is professor of philosophy of religion at the University of Helsinki. He has published widely on, e.g., the pragmatist tradition, the problem of realism, and the philosophy of religion. Vertaisarvioitu peerReviewed